Urban transit infrastructure: Spatial mismatch and labor market power - Felipe Vial Lecaros; Román D. Zárate; Jorge Pérez Pérez (Banco de México, 2023)
This paper estimates the effects of a subway expansion on labor market outcomes in Santiago, Chile. First, we estimate these effects through a reduced-form analysis. We find changes in work locations and wages consistent with a reduction in firms' labor market power in areas where the subway expanded. We then lay out a model with labor market oligopsonies to calculate the welfare gains from the subway expansion. The model allows decomposition of welfare gains into i) efficiency gains from improved worker-firm matching and ii) gains from reducing labor misallocation due to labor market power. We analyze the distributional implications of the subway expansion. We find that workers benefit as firms see reduced profits. In a model with labor market power these welfare gains are larger than in a competitive model.
Keywords: J44; R12; R42; 330; transit infrastructure; labor market power; spatial misallocation; quantitative spatial economics